Thermostability and thermodynamic characterization of sprouted pearl millet ?-amylases for its biotechnological applications (Bangladesh Journal of Scientific and Industrial Research, 2017)
There is an increasing demand for amylolytic products such as glucose syrup in biotechnological industries. Starch liquification by ?-amylase must take place at temperatures higher than the gelatinization temperatures and the use for thermostable ?-amylase is therefore required. Two (or) isotypes namely amy-1 and amy-2 of ?-amylase from pearl millet have been investigated for their thermostability and thermodynamic characterization. Thermal inactivation of ?-amylase follows first order kinetics which varies with time and product during inactivation process. The half-life of ?-1 was 198 mins at 50°C. The Ea (inact) was calculated using Arrhenius plot gave 22.00 KCalmol-1K-1 for ?-1 and 19.44 KCalmol-1K-1 for ?-2. The Z-values were 22.52°C and 25.38°C for ?-1 and ?-2, respectively. The thermodynamic parameters: the enthalpy change of inactivation ?H (inact)  had 87.815 KJmol-1K-1 at 50°C for ?-1 and 78.56 KJmol-1K-1 at 50°C for ?-2. The change in free energy of inactivation ?G (inact) of ?-1 and ?-2 were 105.5 KJmol-1K-1 and 104.33 KJmol-1K-1 at 50°C, respectively. The entropy of inactivation ?S (inact) values for ?-1 and ?-2 are calculated as -54.80 JMol-1K-1 and -79 JMol-1K-1 at 50°C. This suggest that the ?-1 and ?-2 are thermostable.Bangladesh J. Sci. Ind. Res. 52(3), 159-166, 2017